Non-Special Loudspeakers as Speech Test Sources in Natural Acoustics Speech Intelligibility Investigations - Luis Gomez-Agustina; Haydar Aygun; Liji Suseela Thankom Mohan (Acoustics, 2023)
Objective speech intelligibility estimations undertaken in natural acoustics speech communications (NAS) scenarios require the utilization of a speech source that approximates the acoustic characteristics of a human talker. Only a limited number of special speech sources that conform to the specifications in the relevant guidelines are available in the market; however, they can be deemed expensive by professional practitioners and other users. Non-special and affordable loudspeakers are often used in NAS investigations in place of standardized special speech sources without the knowledge of their suitability and results validity. This study aims to examine the suitability of a range of representative common and affordable non-special loudspeakers as a potential alternative to standardized speech sources in NAS indicative or pilot investigations. Frequency response and Speech Transmission Index Public Address (STIPA) experimental results obtained from a reference standardized speech source were compared against results from various non-special loudspeakers measured utilizing diverse and real-world representative combinations of NAS acoustic conditions under controlled laboratory conditions. STIPA mean absolute errors for the alternative speech sources were generally lower than the STIPA method uncertainty and one Just Noticeable Difference (0.03 STI). The findings of this study will inform practitioners of the suitability of affordable loudspeakers when standardized special test loudspeakers are not available.